So much for love : how I survived a toxic relationship - Lambda, Sophie (First Second, 2022)
"Part memoir, part self-help book, So Much For Love offers hilarious and empathetic advice on how to survive a relationship with a master manipulator. Sophie had always been cynical about love--until she meets Marcus. His affection and doting praise melt away her defenses. The beginning of their relationship was a whirlwind romance, but over time she finds herself on uneven footing. Marcus lies. He's violently angry and bewilderingly inconsistent. Yet somehow he always manages to explain away his behavior and to convince Sophie that it's all in her head. The whiplash of this toxic relationship has Sophie's head spinning. When she hits rock bottom, she fights her way out with fierce honesty, irreverent humor, and the help of Chocolat, a wisecracking, booze-drinking bear."--Publisher's website.